SIMULASI WIRELESS MESH NETWORK (WMN) UNTUK MENDUKUNG IMPLEMENTASI NEXT GENERATION NETWORK (NGN) - Nanang Ismail; Adam Faroqi; Lia Kamelia; Rina Mardiati (JURNAL ISTEK, 2011)
Wireless LAN application has been widely used today. One of the wireless topology that cheap but reliable is mesh topology, otherwise known as wireless mesh network (WMN). To support the development of Next Generation Network (NGN), research about wireless mesh network is needed before it is implemented further. This paper represents the preliminary findings of research on the implementation of the WMN for rural areas, especially in areas that will connect between madrasah, majlis ta’lim, pesantren, and others. This paper contains a simulation scenario to determine how the characteristics of wireless mesh networks. This is also done to determine the End-to-End delay, Packet Drop and throughput that occur in the routing process. Simulations conducted in the laboratory using four indoor access point (IAP): 1 as a server, and 3 as a workstation. Routing protocol used in the experiments is OLSR (Optimized Link State Routing). Network monitoring using SNMP and operated on a Linux OS. The simulation results showed that the total bytes for the application packet bigger than packet routing. But the number of routing packets is larger than the application package. Trace routes results showed that the inter-hop in the configuration of the simulation WMN is connected properly.